2009
DOI: 10.1016/j.chom.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Ubiquitin-Specific Protease dUSP36/Scny Targets IMD to Prevent Constitutive Immune Signaling

Abstract: Ubiquitin proteases remove ubiquitin monomers or polymers to modify the stability or activity of proteins and thereby serve as key regulators of signal transduction. Here, we describe the function of the Drosophila ubiquitin-specific protease 36 (dUSP36) in negative regulation of the immune deficiency (IMD) pathway controlled by the IMD protein. Overexpression of catalytically active dUSP36 ubiquitin protease suppresses fly immunity against Gram-negative pathogens. Conversely, silencing dUsp36 provokes IMD-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 58 publications
7
95
1
Order By: Relevance
“…Co-expression of the dUsp36-IR transgene and of an imd-IR transgene, which had been previously shown to efficiently inhibit imd gene expression, 23 did not significantly modify the level of autophagy induction (Fig. 3G) or the cell size reduction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-expression of the dUsp36-IR transgene and of an imd-IR transgene, which had been previously shown to efficiently inhibit imd gene expression, 23 did not significantly modify the level of autophagy induction (Fig. 3G) or the cell size reduction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work identified dUSP36 as a negative regulator of the IMD pathway. 23 We showed that dUSP36 interacts with and deubiquitinates the IMD protein. dUsp36 silencing results in the constitutive activation of this NFkB dependent signaling pathway and consequently of the connected JNK pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of ubiquitinating and deubiquitinating enzymes have been implicated in the negative regulation of the signaling pathway. The ubiquitin-specific protease dUSP36/Scny prevents the accumulation of the activated, K63-ubiquitinated Imd and promotes its K48-linked ubiquitination and subsequent degradation (72). faf is a deubiquitinating enzyme that also was proposed to regulate the ubiquitination state of Imd (73).…”
Section: Regulation Of the Imd Signaling Pathwaymentioning
confidence: 99%
“…Additional negative regulators of the IMD pathway have been identified, mainly acting via ubiquitylation and the degradation of intracellular components of the cascade. [17,[95][96][97][98][99][100][101][102] Altogether, these regulatory components downregulate the IMD cascade following immune stimuli, allowing a balanced AMP response to be re-established once the infection is cleared. [103,104] Another layer of control is provided by the functional compartmentalization of the Drosophila gut.…”
Section: Amp Productionmentioning
confidence: 99%